Optimization of fuzzy controller for minimum time response - Nagi F.; Perumal L. (Elsevier Ltd, 2023)
Minimum time control is desired for non-linear spacecraft-satellite attitude systems to save on-board thruster fuel. The regulatory time depends on the initial attitude of the satellite. Bang-bang control of satellite attitude can be accomplished with fuzzy logic controller using largest of Maxima defuzzification technique. In case of fuzzy controller, earlier studies show that minimum response time depends on the span of the fuzzy controller membership functions. This paper shows how the non-linear relation between the initial attitude of satellite and spans of the fuzzy controller membership functions are optimized to achieve minimum response time by using Nelder-Mead simplex search method. A practical demonstration of fuzzy bang-bang control is demonstrated here by controlling angular position of a single axis attitude application. The pneumatic rotary actuator is controlled in real-time using Matlab-Simulink xPC target environment. 2008 Elsevier Ltd. All rights reserved.